From Rituals to Resilience: Unleashing the Potential of Islamic Kejawen Tradition in Enhancing Community Disaster Awareness - Yasinatul, Puspa Arum; Fitrianto, Achmad Room; Zahroh, Fathimatuz; Haqiqi, Ahmad Syarof; Nazar, Fadlin Ragil; Ramadhana, Aqsha; Gibbons, Nadine Elizabeth (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
Islamic Kejawen tradition is carried out by most Javanese. Islamic Kejawen is an acculturation process between Islamic values and Javanese values, especially in the mysticism aspect. This writing aims to analyse the Islamic Kejawen tradition in Sendang Village and its role in increasing community awareness in dealing with disasters. This research employs a qualitative method including library and field research. The data was obtained using interviews, participation observation, and collecting secondary data. The secondary data was gathered from books, journals, and other scientific works. The study found that the Islamic Kejawen tradition has a significant role in developing community harmony one of which is preserving nature through the annual cultural festival. Furthermore, this tradition has a role in increasing the community’s awareness of avoiding disasters. The Tetek Melek tradition, the jaranan, Grebeg wuyen are the annuals festival conducted in increasing community awareness of their livelihood. The festival conducted is not only for blessing rituals toward the sanctification of God for their wealth but also as media in increasing community awareness for maintaining the environment. In Javanese mysticism, it is explained that God exists in every sphere of activity and natural phenomena as a manifest of the Almighty God’s rewards. The contribution of this research is to provide knowledge about local wisdom in the Kejawen Islamic tradition, especially those found in Sendang Village, Tulungagung Regency. The analysis of this study explains that the Kejawen Islamic tradition can build awareness of disasters.